(untitled) (Journal of Information Technologies in Education (ITE), 2016)
The article describes the actual problem of professional- pedagogical preraration of the teacher of computer science, analyzes found in the research process contradictions between demands of society for increase of quality of education in higher education establishments which prepare teachers of computer skills and insufficient level of readiness of future specialists for work at school, also between the need for enhancement the system of professional training of future teachers and the lack of theoretical and practical basis concerning the formation of proficiency of future teachers in the process of pedagogical practice. It is dermined that quasi-professional activity leads to formation of skills to apply knowledge of fundamental preparation in the sphere of computer science and successfully put it into professional activity. It has been considered the formalization of the model of organization and realization of work experience internship whereas nowadays there is a need of technologisation of this process by the leaders of pedagogical practice on the basis of secondary schools. This survey gives an opportunity to analyze the condition of pedagogical practice of future teachers of computer skills from viewpoint of trainees.